Геодинаміка Теребле-Ріцького техногенного полігону - Третяк, К.Р.; Кульчицький, А.Я.; Сідоров, І.С. (Геодинаміка, 2009)
On the basis of results of the complex analysis of the given geodetic measurements and geological studying of territory of Tereblja-Riksky derivational hydroelectric power station the geodynamic model of interaction of engineering constructions and the geological environment is created. Recommendations for carrying out of monitoring of geodynamic processes are offered.